2018
DOI: 10.3390/rs10101617
|View full text |Cite
|
Sign up to set email alerts
|

A New Methodology for Estimating the Surface Temperature Lapse Rate Based on Grid Data and Its Application in China

Abstract: Land surface temperature (LST) is an important parameter in the study of the physical processes of land surface. Understanding the surface temperature lapse rate (TLR) can help to reveal the characteristics of mountainous climates and regional climate change. A methodology was developed to calculate and analyze land-surface TLR in China based on grid datasets of MODIS LST and digital elevation model (DEM), with a formula derived on the basis of the analysis of the temperature field and the height field, an ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 51 publications
1
5
0
Order By: Relevance
“…The ELRT produces smaller rates for the decrease of temperature with height. This is not a peculiar behaviour for South America as it has been already identified for the Himalayas (Romshoo et al ., 2018), the Tibetan Plateau (Wang et al ., 2018; Zhang et al ., 2019), China (Qin et al ., 2018) and for the Arctic (Gardner et al ., 2009). The annual cycle is also well represented by all data sources used; however, SAMeT displayed values closest to the observations.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…The ELRT produces smaller rates for the decrease of temperature with height. This is not a peculiar behaviour for South America as it has been already identified for the Himalayas (Romshoo et al ., 2018), the Tibetan Plateau (Wang et al ., 2018; Zhang et al ., 2019), China (Qin et al ., 2018) and for the Arctic (Gardner et al ., 2009). The annual cycle is also well represented by all data sources used; however, SAMeT displayed values closest to the observations.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…Nevertheless, it has been observed that some environmental variables (i.e., solar incidence, moisture, land cover characteristics) cause interference of NSTLR estimated from LST data [18,34]. Therefore, it has been suggested normalizing LST data with respect to environmental variables, potentially improving the accuracy of estimation of NSTLR from satellite information [8,35]. This approach has been less explored and requires further evaluation, particularly for the relatively less utilized medium resolution sensors.…”
Section: Introductionmentioning
confidence: 99%
“…In the aspect of estimation methods, the simple linear regression model solved with ordinary least squares (OLS) method was frequently used to calculate the SATLR (Rolland, 2003;Blandford et al, 2008;Kattel et al, 2018). As the simple linear regression model, a kind of global model, could lead to many problems, including the spatial non-stationarity, when there was complex terrain and climatic condition in a large region, observational stations were usually divided into several groups and the SATLRs of each group were estimated separately (Fotheringham et al, 2002;Zhai et al, 2016;Qin et al, 2018). The division criterion was not always the same between different literatures.…”
Section: Introductionmentioning
confidence: 99%